(untitled) (BIRDEM Medical Journal, 2019)
Pulmonary sclerosing hemangioma is a rare benign neoplasm of the lung and predominantly occurs in female patients. Commonly, it presents as asymptomatic solitary pulmonary nodule on chest radiograph. We report a case of pulmonary sclerosing hemangioma who presented with fever and chest x-ray and computed tomography revealed cavitary lesion and mediastinal lymphadenopathy . The chest imaging findings were mimicking bronchial carcinoma. On histopathology and immune-cyto-histochemistry, we found her as having pulomonary sclerosisng hemangioma.The patient is now on follow up without any progression of the disease for last two months. Birdem Med J 2019; 9(3): 251-253